Prevalence and quantitative microbial risk assessment of Salmonella in pork value chain in Hung Yen province, Vietnam - Sinh Dang Xuan; Hung Nguyen-Viet; Unger, Fred; Phuc Pham Duc; Ngan Tran Thi; Grace, Delia; Makita, K. (International Livestock Research Institute, 2016)
Objectives: In Vietnam, pork accounts for 75% of total meat consumed by households. However, pork may contain high levels of microbial contaminants such as Salmonella and Escherichia coli which can cause harm to consumers. We conducted the first risk assessment for salmonellosis risk through boiled pork consumption in Hung Yen, Vietnam. Method: A total of 646 samples were collected repeatedly from pig farms (36), slaughterhouses (26) and pork shops (108) in Hung Yen between April 2014 and February 2015. Cooking and consumption behaviour were studied through focus group discussions. Data were used for a quantitative microbial risk assessment (QMRA) to estimate the salmonellosis risk from boiled pork consumption using @Risk. Published data on reduction and cross-contamination of Salmonella during cooking were also used for the assessment. Results: Overall Salmonella prevalence at pig farms, slaughterhouses and pork shops were 36.1%, 35.3% and 34.2%, respectively. Salmonella contamination in pork sold at market was 44.4% and an average concentration of 7.4 MPN/g was recorded. QMRA results for Salmonella show a high risk of incidence for the assessed population. The risk in different level of urbanization, and sensitivity of factors are being analysed. Conclusion: High Salmonella contamination in pork aligned with QMRA results demonstrate the health risks for consumers. Feasible mitigations to improve hygiene practices are required to reduce the risk for the consumer.